Initiating women in Freemasonry : the adoption rite - Snoek, Joannes Augustinus Maria, 1946- (Aries Book Series, 2012)
Freemasonry is generally regarded a male phenomenon. Yet, both before 1723 and since 1744, women were initiated as well. This book is about the rituals, used for the initiation of women in the Adoption Lodges, since the middle of the 18th century. It describes their contents, roots and creation before reviewing and conceptualising their development in the past three centuries. It analyses the different families of rituals within the Adoption Rite, and gives an overview of specific developments, showing how the rituals were adapted to their changing contexts. Apart from its relevance for the history of Freemasonry in general and the Adoption Rite in particular, the book also writes a hitherto unknown chapter of women's history. Of particular interest for the history of feminism is the chapter about the 20th century, which could only be written now that the documents concerning it, which had been moved to Moscow in 1945, had been returned in 2000.